Social Media as an Effective Solution to Dealing with Violations of the Professional Code of Ethics: An Overview of Violations of the Police Code of Ethics - Alamsyah, Feiruz Rachmita; Putra, Bara Setiadi (Indonesia Media Law Review, 2023)
The legal profession plays a crucial role in upholding justice and maintaining public order. It is the responsibility of legal professionals, including the police, to carry out their duties with integrity and high ethical standards. The code of ethics for the legal profession sets out the expected standards of behavior for its members. However, in practice, police officers often violate these ethical guidelines. In this paper, the author employs the normative legal research method, which examines legal rules from a vertical or horizontal perspective. The normative legal research method utilized in this paper adopts a normative juridical approach, focusing on the relevant laws and regulations. To address violations of the code of ethics by the police, the Professional and Security Division of the Indonesian National Police (referred to as Propam Polri) has established social media platforms for citizens to report complaints. As discussed earlier, citizens are required to submit a documented report when filing complaints. Effective complaint handling mechanisms are vital in addressing violations of the legal profession's code of ethics on social media. It is important to have clear internal policies, secure channels for lodging complaints, independent investigations, appropriate sanctions, and procedures for improvement and ongoing monitoring. By implementing such mechanisms, legal practitioners can uphold the integrity and ethical standards of their profession in their use of social media. Furthermore, appropriate consequences can be applied for any violations of the code of ethics that occur.